Technical execution, properties, method of dissemination, target consumer, acceptance and evaluation of the results of disinformation - Viktor PORADA; Anton LISNÍK (Košická bezpečnostná revue)
Following on from the issue of propaganda, disinformation, psychological and mental warfare as a power tool in the globalized world, the life cycle of disinformation, the news legend and the creators of disinformation, the issue of the technical implementation of disinformation, its properties and methods of its dissemination is presented as a subsequent addition to the issue.Keywords: The cycle of disinformation, the orderer of disinformation, the planning of disinformation, the creator, the purpose, the goal, the content, the type of disinformation, the news legend, the social, cultural, religious, historical, geopolitical environment of disinformation